Peran Influencer Tiktok @Shalmafadilla_ Dalam Promosi Program Au Pair Dan Ausbildung - Puteri Anugerah Maharani; Tira Fitriawardhani; Julyanto Ekantoro (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study aims to analyze the role of TikTok influencer @shalmafadilla_ in promoting Au Pair and Ausbildung programs. The research employs a descriptive qualitative approach using the AIDA theory (Attention, Interest, Desire, Action) as the analytical framework. Data were collected through observation of TikTok content published between January and November 2025, online interviews with the influncer as the main informant, and five active followers who frequently interacted with Au Pair and Ausbildung related content. Documentation, including audience comments, views, and engagement metrics, was also used to support the analysis. The findings indicate that the influencer successfully captures audience attention through visual content and personal storytelling, builds interest through clear and consistent information delivery, generates desire through emotional appeal and credibility, and encourages audience action by motivating further information seeking behaviors. This study concludes that TikTok influencers play a strategic role as persuasive communicators in promoting international education and work programs.